Synthesis and performance evaluation of ZnO/CdS photoanodes with copper sulfide (Cu2S) and carbon counter electrodes - Pooja B. More; Chaitali V. Jagtap; Vishal S. Kadam; Mu. Naushad; Nithesh Naik; Pavan Hiremath; Habib M. Pathan (Scientific Reports)
Abstract The present study demonstrates the synthesis of compact ZnO layers using CdS sensitized on ZnO as a photoanode with copper sulfide (Cu2S) and carbon as a counter electrode (CE). In this study, a compact ZnO layer was fabricated using the simple and low-cost successive ionic layer adsorption and reaction (SILAR) method, and Cu2S CE films were synthesized using the chemical bath deposition method. Various characterizations, such as X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS), confirmed the formation of ZnO and CdS sensitizations on the ZnO . UV-visible spectroscopy revealed that the bandgaps of the ZnO and Cu2S films were 3.2 and 1.3 eV, respectively. Furthermore, the morphology of the ZnO films was optimized by varying the number of SILAR cycles. Scanning electron microscopy revealed the formation of a nanorod compact layer (CL) and the porous nature of the ZnO photoanode films. However, the porosity increased with the number of SILAR cycles. Various parameters, such as the current density, voltage, fill factor, and efficiency, were measured using the J-V characteristics. The highest 0.85% efficiency was achieved by using the ZnO compact film with 30 SILAR cycles for the Cu2S CE. Furthermore, the study revealed that the Cu2S counter electrode had a higher electrocatalytic response than the carbon CE.